The toxicity of ammonia as a fumigant to dry wood termite (Cryptotermes cynocephalus L.) on sengon wood - Irfan, Abdul Mubaraq; Sakti Harahap, Idham; Pudjianto (Universitas Lampung, 2023)
Wood-based packaging material is usually made from low-quality kind of wood, making it a potential medium for carrying or housing wood-destructive organisms. The objective of this research was to investigate the toxicity of ammonia as a fumigant for controlling the dry-wood termite, Cryptotermes cynocephalus. Ammonia was applied as ammonium hydroxide (NH4OH) 25%, which was placed inside the fumigation chamber. At 2.25 cm wood thickness, toxicity tests were performed using 3 levels of NH4OH doses (0, 700, and 3800 mL/m³) and 4 levels of exposure (4, 6, 8, and 10 hours). The toxicity of ammonia fumigant at 1.25 cm wood thickness was assessed using 6 dose levels of NH4OH (0, 200, 378, 587, 1732, and 4188 mL/m³) for 4 hours of exposure. The LD50 and LD90 values of ammonia against the dry-wood termite, C. cynocephalus, inside the sengon wood at 2.25 cm thickness after 4 hours of exposure were 3263 mL NH4OH/m³ and 22,781 mL NH4OH/m³, respectively. Moreover, for 1.25 cm wood thickness, for the same exposure duration (4 hours), the LD50 and LD90 values of ammonia fumigant were 541.594 mL NH4OH/m³ and 1432.125 mL NH4OH/m³, respectively. Meanwhile, for 0.25 cm wood thickness, the LD50 and LD90 values were 67.67 mL of NH4OH/m³ and 241.140 mL NH4OH/m³, respectively. In addition, for 2.25 cm wood thickness, the LD50 and LD90 values of ammonia fumigant were lower when the exposure time was longer (2149 and 10,722 mL NH4OH/m³ for 6 hours of exposure, and 1373 and 8705 mL NH4OH/m³ for 8 hours of exposure).